Analysis of the Drivers Influencing Burnout among Staff in Amir Al-Momenin Hospital of Zahedan - Alireza Sargolzaei (Journal of Global Pharma Technology, 2018)
One of the concepts which has received a great deal of attention during the recent years from the organizational-industrial psychologists is the fatigue, exhaustion, lassitude, torpidity, languor and indolence in the job operators which is known as the so-called job burnout. The objective of the present study is to identify and prioritize the effectors which influence the job burnout in the staffs working in Amir Al-momenin hospital. The present study is an applied research in terms of the methodology it adopts because the indices extracted from the study literature are identified and rated according to the study conceptual model and the organizations can take advantage of the results presented herein to device the best strategy and choose the most optimum indices and put them into practical use. In the present study, the study theoretical principles and the study background have been drawn out of the library searches and the study of university articles and journals and also it has to be mentioned that the field study methods and thorough analysis of the study population have been applied as a source of collecting statistical information for testing the study hypotheses. The study population in the present study is basically consisted of the entire managers working in Amir Al-momenin hospital the total number of whom reaches to 150 individuals and subsequently a number of 108 individuals were selected as the study sample volume by making use of Morgan’s table. To analyze the data, AHP method has been employed along with making use of Expert Choice software. The results of the study indicated that environmental, organizational, individual and vocational factors are found of a great effect on the job burnout in the staffs.Keywords: Job burnout, Environmental factors, Organizational factors, Individual factors, Vocational factors.